The efficacy of vaginally compared to orally administered misoprostol in inducing labor in term early ruptured membrane - Hariadi Hariadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Misoprostol is now widely used as an agent for the induction of labor, although the effectiveness of its use in premature rupture of the membrane is questionable.Objectives: To compare the effectiveness of vaginal versus oral administration of misoprostol for induction of labor in term pregnancy with premature rupture of the membranes.Study Design: A retrospective cohortMaterials and Method: The study was conducted at Dr. Sardjito General Hospital Yogyakarta from January 1999 to November 2001. Data were taken from medical record. The inclusion criteria were gestational age of 37 weeks not yet in labor with premature rupture of membranes, singleton gestation, cephalic presentation, reactive fetal heart pattern, and Bishop score s 4. The pregnancy that is complicated by diseases were excluded. Vaginal administration of misoprostol was considered as the exposed group while oral administration was as control. Misoprostol 50 mg had been at six hours interval, for maximal dose of 200 pg. Variable outcomes were effectiveness, duration of induction, mode of delivery, side effects, and newborn asphyxia. Data were processed with SPSS for Window version 10.0, t-Test, chi-square test, relative risk, and binary logistic regression were used for statistical analysis.Result: During the period of three years, there had been 249 cases of premature rupture of membranes that met the inclusion and exclusion criteria consisting of 88 cases exposed group and 88 cases of control. The success rate of the vaginal misoprostol was 80.70% compared to 87.50% in the oral misoprostol with p > 0.05. The cesarean rate from vaginal misoprostol and oral misoprostol were 8.00% versus 3.40% respectively (RR 2.23 and 95% CI 0.62-8.73), the rate of asphyxia in the newborn was 29.50% versus 26.10% (RR 1.13 and 95% CI 0.70-1.82). The rate of side effect, hyperstimulation, was 5.70% versus 1.10% (RR 5.00 and 95% CI 0.60-41.93) in the vaginal group. The length of induction vaginal and oral misoprostol were 10.00 Â± 4.86 and 9.76 Â± 4.56 hours. There was one case of cesarean section followed with hysterectomy due to urine atony in the vaginal group.Conclusion: The success rate of vaginal misoprostol induction was slightly lower than oral, but it was not statistically significant, as well as the incidence of the first minute of asphyxia. The interval between the administration of drug to complete dilatation in the vaginal and oral group was not different. The rate of cesarean section and hyperstimulation was higher in the vaginal group.Key words: misoprostol - oral and vaginal - effectiveness - premature rupture of membranes - neonatal .asphyxia